Hypertension and happiness across nations - David G. Blanchflower; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2007)
A modern statistical literature argues that countries such as Denmark are particularly happy while nations like East Germany are not. Are such claims credible? The paper explores this by building on two ideas. The first is that psychological well-being and high blood-pressure are thought by clinicians to be inversely correlated. The second is that blood-pressure problems can be reported more objectively than mental well-being. Using data on 16 countries, the paper finds that happier nations report lower levels of hypertension. The paper's results are consistent with, and seem to offer a step towards the validation of, cross-national estimates of well-being.
urn:nbn:de:101:1-20080416312
Keywords: 330; Lebenszufriedenheit; Gesundheit; Europa